Role of the heterogenous structure of ZnO/MnFeO3 in enhancing Bi-functional electrocatalyst for alkaline water electrolysis - Malavika Sadanandan; Tushar Chauhan; Krishna Kanta Haldar (Nano Express, 2024)
An electrocatalyst, Zn-doped 3D porous MnFeO _3 , is developed and investigated for its efficacy in alkaline water electrolysis. The electrocatalyst is synthesized through a sol–gel method and characterized comprehensively. Incorporating zinc (Zn) doping enhances the electrocatalytic activity of the MnFeO _3 structure, rendering it suitable for bifunctional performance in alkaline water electrolysis. The Zn-doped 3D porous MnFeO _3 was studied electrochemically, and the results showed that it has a very low overpotential of 460 mV for OER and 441 mV for HER in order to achieve a current density of 100 mA cm ^−2 , conducted in a 1 M KOH medium. The catalyst’s porous 3D structure offers a large surface area, enhancing its ability to interact with the electrolyte and promote H _2 and O _2 gas evolution. The Zn-doped 3D porous MnFeO _3 exhibits improved stability for 24 h, with only a 17% loss in current density at 10 mA cm ^−2 . The electrochemical performance of the Zn-doped 3D porous MnFeO _3 electrocatalyst is evaluated through various electrochemical techniques, highlighting its promising potential for practical applications in alkaline water electrolysis systems.